Assessment of the practices of internal control system in the public sectors of Malaysia / Mohamad Azizal Abd Aziz, Jamaliah Said and Md. Mahmudul Alam - Abd Aziz, Mohamad Azizal; Said, Jamaliah; Alam, Md. Mahmudul (Universiti Teknologi MARA Cawangan Selangor, 2015)
This study attempts to assess the status of current practices of internal control system in different service schemes of the public sector in Malaysia. This study collected primary data through a set of questionnaires given to the heads of 109 departments and agencies under 24 federal ministries, including the Prime Minister Department, in Malaysia. The data were collected on the basis of the opinion on 10 factors of internal control practices in the department or agency using a seven-point Likert scale. The data were analyzed using descriptive statistics and factor analysis. The reliability of the data was tested using the Cronbach’s alpha test, and the validity of the data was tested by checking the normality of data through the Shapiro–Wilk test and graphical method. Overall, 86.2% of the respondents mentioned that they practiced internal control system in their department. However, the priority of these 10 factors of internal control differs among the service schemes. The internal control system of the financial scheme group is strong, but its emphasis on the documentation is only average. By contrast, the internal control in the engineering, information system, education, and medical and health schemes is below the overall average internal control score. The public sector in Malaysia should focus more on internal control and its proper assessment system to become a reliable and efficient sector.